Ultra-small and broadband polarization splitters based on double-slit interference - Sun, Chengwei; Li, Hongyun; Qihuang Gong; Chen, Jianjun (Applied Physics Letters, 2016)
An ultra-small and broadband polarization splitter is numerically and experimentally demonstrated based on the double-slit interference in a polymer-film-coated double-slit structure. The hybrid slab waveguide(air-polymer-Au) supports both the transverse-magnetic and transverse-electric modes. The incident beam from the back side can excite these two guided modes of orthogonally polarized states in the hybrid structure. By exploiting the difference slit widths and the large mode birefringence, these two guided modes propagate to the opposite directions along the front metal surface. Moreover, the short interference length broadens the operation bandwidth. Experimentally, a polarization splitter with a lateral dimension of only about 1.6 μm and an operation bandwidth of 50 nm is realized. By designing the double-slit structure in a hybrid strip waveguide, the device dimension can be significant downscaled to about 0.3 × 1.3 μm2. Such an ultra-small and broadband polarization splitter may find important applications in the integrated photonic circuits.